HOSPITAL WASTE MANAGEMENT -A GROWING HEALTH CONCERN - Sofia Shehzad (Gandhara University, 2018)
In this era of startling developments in the medical field there remains a serious worry about the  hazardous  potential  of  various  by  products  which  if  not  properly  addressed  can  lead  to consequences of immense public concern. Hospitals and other health care facilities generate waste products which are evidently hazardous to all those exposed to its potentially harmful effects. Need for effective legislation ensuring its safe disposal is supposed to be an integral part of any country's health related policy. This issue is of special importance in developing countries like Pakistan which in spite of framing various regulations for safeguarding public health, seem to overlook its actual implementation. The result unfortunately  is the price wehave to pay not only in terms of rampant spread of crippling infections but a significant spending of health budget on combating epidemics which could easily have been avoided through effective waste disposal measures in the first place. Waste classified under the heading  'bio-hazardous' includes any infectious or potentially infectious  material  which  can  be  injurious  or  harmful  to  humans  and  other  living  organisms. Amongst the many potential sources are the hospitals or other health  delivery centres which are ironically  supposed to be the centres of infection control and treatment. Whilst working in these setups, health care workers such as doctors, nurses, paramedical staff and sanitation workers are actually the ones most exposed and vulnerable to these challenges.  Biomedical waste may broadly be classified into Infectious and toxic waste. Infectious waste includes sharps, blood, body fluids and tissues etcwhile substances such as radioactive material and by-products of certain drugs qualify  as toxic waste. Furthermore health institutions also have to cater for general municipal waste such as carton boxes, paper and plastics. The World Health Organisation  has  its  own  general  classification  of  hospital  waste    divided  into  almost  eight categories of which almost  15% (10% infectious and 5% toxic) is estimated to be of a hazardous nature while the remaining 85% is general non hazardous content.1A recent study from Faisalabad, Pakistan has estimated hospital waste generation around 1 to 1.5 kg / bed /day for public sector hospitals in the region,2while figures quoted from neighbouring India are approximately 0.5 to 2 KG / hospital  bed  /day.3   Elsewhere in the  world variable  daily  hospital waste production  has been observed ranging from as low as 0.14 to 0.49 kg /day in Korea4 and 0.26 to 0.89 kg/day in Greece5to as high as 2.1 to 3.83 kg/day in Turkey6 and 0.84 to 5.8 kg/day in Tanzania.7Ill effects of improper management of hospital waste can manifest as nosocomial infections or occupational hazards such as needle stick injuries. Pathogens or spores can be borne either through the oro-faecal or respiratory routes in  addition  to direct inoculation  through contact with infected  needles  or  sharps.  Environmental  pollution  can  result  from  improper  burning  of  toxic material leading to emission of dioxins, particulate matter or furans into the air. The habitat can also be affected by illegal dumping and landfills or washing up of medical waste released into the sea or river. Potential organisms implicated in diseases secondary to mismanagement of hospital waste disposal include salmonella, cholera, shigella, helminths, strep pneumonia, measles, tuberculosis, herpesvirus, anthrax,  meningitis, HIV,  hepatitis  and candida etc. These infections can cause a considerable strain on the overall health and finances of the community or individuals affected. The basic principal of Public health  management i.e  'prevention  is better than  cure' cannot be more stressed in this scenario as compared to any other health challenge.  Health facilities must have a clear policy on hazardous waste management. To ensure a safe environment hospitals need to adopt  and  implement  international and  local  systems  of  waste  disposal.    Hospital  waste management  plan  entails  policy  and  procedures  addressing  waste  generation,  accumulation, handling, transportation, storage, treatment and disposal.  Waste needs to be collected in marked containers usually  colour coded and  leak  proof. Segregation at source is of vital importance. The standard practice in many countries is the Basic Three Bin System ie to segregate the waste into RED bags/ boxes for sharps, YELLOW bags for biological waste and BLUE or BLACK ones for general/ municipal waste. All hospital staff needs to be trained in the concept of putting the right waste in relevant containers/ bags. They need to know that  more than  anything  else  this  practice  is  vital  for  their  own  safety.  The  message can  be reinforced through appropriate labelling on the bins and having posters with simple delineations to avoid mixing of different waste types. Sharps essentially should be kept in rigid, leak and puncture-resistant containers which are tightly lidded and labelled. Regular training sessions for nurses and cleaning staff can be organised as they are the personnel who are more likely to deal with waste disposition at the level of their respective departments. Next of course is transportation of waste products to the storage or disposal.  Sanitary staff and janitors must be aware of the basic concepts of waste handling  and should wear protective clothing, masks and gloves etc, besides ensuring regular practice of disinfection and sterilization techniques.8Special trolleys or vehicles exclusively designed and reserved for biomedical waste and operated by trained individuals should be used for transportation to the dumping or treatment site. Biomedical waste treatment whether on site or off site is a specialised entity involving use of chemicals and equipment intended for curtailing the hazardous potential of the material at hand. Thermal treatment via  incinerators, not only results in combustion of organic substances but the final  product in the form of non-toxicash is only  10  to 15% of the original  solid mass of waste material  fed  to the  machine.   Dedicated autoclaves  and  microwaves can also be  used for  the purpose of disinfection. Chemicals such as bleach, sodium hydroxides, chlorine dioxide and sodiumhypochlorite are also effective disinfectants having specialised indications.  Countries  around  the  world  have  their  own regulations  for waste management.  United Kingdom practices strict observance of Environmental  protection act 1990, Waste managementlicensing  regulations  1994  and  Hazardous  waste regulations  2005  making  it  one  of  thesafest countries in terms of hazardous waste disposal. Similar regulations specific for each state have been  adopted  in  United  States  following  passage  of  the  Medical  Waste tracking  act 1988.  In Pakistan,  every  hospital  must comply with  the  Waste Management  Rules  2005  (Environment Protection Act  1997),  though  actual compliance is far from satisfactory. It  is high  time that  the government and responsible community organisations shape up to seriously tackle the issue of bio hazardous waste management through enforcement of effective policies and standard operating procedures for safeguarding  the health  and lives  of the public in  general and  health  workers in particular.